Sociodemographic and lifestyle correlates of exclusive breastfeeding practices among mothers on antiretroviral therapy in the Eastern Cape, South Africa - Daniel Ter Goon; Anthony Idowu Ajayi; Oladele Vincent Adeniyi (BMC, 2021)
Abstract Background Exclusive breastfeeding (EBF) is associated with a reduction of postnatal HIV transmission and optimal infant growth. Given that the factors influencing exclusive breastfeeding are multi-factorial and context-specific, we examined the prevalence and factors associated with exclusive breastfeeding practice in the first 6 months among mothers on antiretroviral therapy in the Eastern Cape, South Africa. Methods This was a cross-sectional study conducted between January to May 2018, on 469 parturient women enlisted in the prevention of mother-to-child HIV transmission cohort study in the Eastern Cape. Mothers were asked to recall whether they breastfed their infant exclusively with breast milk from birth and if so, to state how long they did. We collected relevant sociodemographic, lifestyle, and maternal information by interview. Bivariate and multivariable logistic regression analyses were fitted to determine the sociodemographic and lifestyle factors associated with exclusive breastfeeding practice. Results The prevalence of six-month exclusive breastfeeding, measured since birth, was 32.0%. E Exclusive breastfeeding's prevalence was significantly higher among married women (36.8%), unemployed women (36.6%), non-smokers (32.7%), and those who never drank alcohol (37.0%). Unemployed women (adjusted odds ratio [AOR] 1.66, 95% Confidence Interval [CI] 1.08-2.56) and those with grade 12 or less level of education (AOR 2.76, 95% CI 1.02-7.49) had a higher likelihood of practising EBF for 6 months since birth while mothers who consumed alcohol (AOR 0.54, 95% CI 0.34-0.85) were less likely to practice EBF for 6 months. Conclusions The prevalence of six-month exclusive breastfeeding in the study, although comparable with sub-Saharan Africa and worldwide prevalence, remains suboptimal. Advocacy campaigns on EBF must target alcohol cessation and the creation of a favourable workplace environment for lactating mothers.